Six new species of Australocosmica Köhler, 2011 from the Kimberley islands, Western Australia (Mollusca: Pulmonata: Camaenidae) - Criscione, Francesco; Köhler, Frank (Zootaxa, 2013)
The Western Australian Kimberley region harbours a diverse fauna of camaenid land snails characterised by marked patterns of narrow range endemism. The recently described genus Australocosmica comprised three species that are endemic to single offshore islands or island groups. Material of a further seven candidate species recognised by the late Alan Solem has been examined. Six of these manuscript species, NSP 40 (= A. rotunda n. sp.), NSP 76 (= A. pallida n. sp.), NSP 77 (= A. buffonensis n. sp.), NSP 78 (= A. bernoulliensis n. sp.), NSP 79 (= A. crassicostata n. sp.), and NSP 80 (= A. nana n. sp.), are here newly described based on examination of shell morphology and penial anatomy. Based on our findings, we are presenting an updated generic diagnosis of Australocosmica. Statistical analyses revealed that species exhibit similar shell characters (colouration, sculpture, dimensions), which render the delimitation of species based only on shells difficult. However, species were found to differ significantly in their penial anatomy. Although the material studied was not suitable for DNA extraction, the anatomical differences were considered sufficient to permit the description of distinct species.